Non-ionizing electromagnetic radiation - health aspects - Radovanovic, Lidija; Miletic, Miljan; Nikolić, Mladen (PONS - medicinski časopis, 2026)
The accelerated development of mobile telecommunications, the widespread use of modern wireless technologies for the transmission of information and energy, as well as the growing use of electromagnetic devices in medical practice, have led to significant changes in the quality of the environment. Modern man is continuously exposed to non-ionizing electromagnetic radiation of various origins, which has raised concerns about the potential health effects of long-term exposure of the population to artificial sources of electromagnetic fields. Numerous studies have been aimed at examining the possible connection between the level of electromagnetic exposure and the frequency of certain health disorders. In order to assess the level of exposure of the population, measurements of electric, magnetic and electromagnetic fields were carried out in residential and working areas, in the frequency range from 0 Hz to 3.5 GHz. The measurements were carried out in areas identified as "hot spots", as well as in the immediate vicinity of sources of electromagnetic radiation, including power lines and wireless computer networks. The results obtained represent the basis for assessing the compliance of the measured values with applicable national and international regulations and recommendations, as well as for considering potential implications for public health.
Keywords: Electromagnetic exposure, non-ionizing radiation, mobile telephony, public health